(untitled) (Revista de Ciências Agroveterinárias, 2015)
The objective was to evaluate the rooting of Japanese pittosporum (Pittosporum tobira) during the application of different doses of indole acetic acid (IAA). The plant material consisted of 10 cm long cuttings, which were treated with different concentrations of IAA (0; 1,000; 2,000; 3,000; and 4,000 mg L-1) for 10 seconds. After that, the cuttings were grown in polyethylene bags containing commercial substrate and vermiculite, at the nursery under greenhouse conditions and subjected to environmental conditions. After 120 days, we evaluated the percentage of survival and rooted cuttings, leaf area index (LAI), and root length, using the UTHSCSA software. Cutting survival was not influenced by the concentration of IAA. The rooting percentage and LAI showed quadratic behavior as concentrations of IAA increased. The best rooting responses were using 2,000 mg L-1 of IAA, resulting in maximum dose of technical efficiency (MDTE) to 2,175.00 mg L-1. The greatest length of roots per cutting was found at intermediate concentrations of IAA, with MDTE of 1,911 mg L-1. The use of 2,000 mg L-1 of IAA benefits the rooting of P. tobira cuttings.